PREFERENSI KONSUMEN ATAS PEMBARUAN KEMASAN PRODUK KERUPUK LAMUK (STUDI KASUS JAJANAN TRADISIONAL KHAS DESA KALIRONG, KEDIRI): (Studi Kasus Jajanan Tradisional Khas Desa Kalirong, Kediri) - Wibowo, Moch. Agus Suryo; Artini, Widi; Sidhi, Eko Yuliarsha; Lisanty, Nina (JURNAL AGRICA, 2025)
Lamuk Crackers, a beloved traditional snack from Kalirong Village in Kediri, exemplifies an innovative way to repurpose cassava starch waste. Known for their distinctive flavour and cost-effective production, these crackers offer several advantages. However, they also face obstacles in today's competitive snack market, particularly in terms of packaging innovation. This study aims to understand consumer preferences for Lamuk Crackers better, emphasising the significance of packaging development and proposing strategies to improve packaging that can boost the product’s market position. We adopted a quantitative research approach, using a structured questionnaire as our primary data collection tool for surveys. Using simple random sampling, we gathered responses from 185 consumers who had previously tried Lamuk Crackers. Data analysis was performed using logistic regression to identify key factors that influence purchasing decisions. The findings reveal that innovative packaging, such as aluminium foil in a standing pouch design, considerably enhances consumer appeal and preference. Important factors influencing buying choices include product quality, materials, shelf life, brand loyalty, and price. There is a clear link between innovative packaging and the product’s visual appeal, which helps communicate its premium quality, improves protection, and prolongs shelf life—all of which affect consumer decisions. To grow the market share, implementing a comprehensive marketing strategy is essential, using social media, e-commerce platforms, and collaborations with retail partners. This approach aims to preserve the authentic identity of Lamuk Crackers while boosting its competitiveness amid a rapidly changing marketplace.